Maternal rank influences the outcome of aggressive interactions between immature chimpanzees. (February 2015) - Markham, A. Catherine; Lonsdorf, Elizabeth V.; Pusey, Anne E.; Murray, Carson M.
Abstract : For many long-lived mammalian species, extended maternal investment has a profound effect on offspring integration in complex social environments. One component of this investment may be aiding young in aggressive interactions, which can set the stage for offspring social position later in life. Here we examined maternal effects on dyadic aggressive interactions between immature (<12 years) chimpanzees. Specifically, we tested whether relative maternal rank predicted the probability of winning an aggressive interaction. We also examined maternal responses to aggressive interactions to determine whether maternal interventions explain interaction outcomes. Using a 12-year behavioural data set (2000–2011) from Gombe National Park, Tanzania, we found that relative maternal rank predicted the probability of winning aggressive interactions in male–male and male–female aggressive interactions: offspring were more likely to win if their mother outranked their opponent's mother. Female–female aggressive interactions occurred infrequently (two interactions), so could not be analysed. The probability of winning was also higher for relatively older individuals in male–male interactions, and for males in male–female interactions. Maternal interventions were rare (7.3% of 137 interactions), suggesting that direct involvement does not explain the outcome for the vast majority of aggressive interactions. These findings provide important insight into the ontogeny of aggressive behaviour and early dominance relationships in wild apes and highlight a potential social advantage for offspring of higher-ranking mothers. This advantage may be particularly pronounced for sons, given male philopatry in chimpanzees and the potential for social status early in life to translate more directly to adult rank. Highlights: We examined the outcome of aggressive interactions between wild immature chimpanzees. Offspring were more likely to win if their mother outranked their opponent's mother. Direct maternal interventions were rare in aggressive interactions. This suggests that maternal interventions do not often explain interaction outcome.